2006
DOI: 10.1016/j.otohns.2006.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guideline: Acute otitis externa

Abstract: This is the first, explicit, evidence-based clinical practice guideline on acute otitis externa, and the first clinical practice guideline produced independently by the AAO-HNSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
230
0
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(249 citation statements)
references
References 106 publications
(136 reference statements)
2
230
0
13
Order By: Relevance
“…40 Which topical antibiotic agent is best for external otitis is unclear. 41 High-quality studies that evaluated quinolone versus nonquinolone topical solutions are limited. A systematic review of 13 metaanalyses confirmed that topical antibiotic agents were superior to placebo and noted a statistically significant advantage of quinolone agents over nonquinolone agents in the rate of microbiologic cure (P = .035).…”
Section: External Otitis Tympanostomy Tubeassociated Otorrheamentioning
confidence: 99%
“…40 Which topical antibiotic agent is best for external otitis is unclear. 41 High-quality studies that evaluated quinolone versus nonquinolone topical solutions are limited. A systematic review of 13 metaanalyses confirmed that topical antibiotic agents were superior to placebo and noted a statistically significant advantage of quinolone agents over nonquinolone agents in the rate of microbiologic cure (P = .035).…”
Section: External Otitis Tympanostomy Tubeassociated Otorrheamentioning
confidence: 99%
“…Data are shown as means ± SEM (n = 6) Ear drops containing gentamicin are often used in human and veterinary medicine for the treatment of external otitis since staphylococci and Pseudomonas aeruginosa are frequently present in such conditions. Because of a potential Acta Veterinaria Hungarica 63, 2015 irreversible ototoxic effect (Matz et al, 2004), gentamicin-containing products cannot be used in cases with a perforated tympanic membrane (Rosenfeld et al, 2006). Although the present studies were conducted on monolayer IPEC-J2 cells, our results suggest that gentamicin alone or supplemented with 1% DMSO cannot penetrate through the intact tympanic membrane into the inner ear.…”
Section: Resultsmentioning
confidence: 60%
“…Although AOE is primarily a local disease, it may be more severe and invasive in cases where the patients' immune system is suppressed. Edema and sensitivity in the EAC are noted in otoscopic examinations [2] .…”
Section: Introductionmentioning
confidence: 99%